PENGEMBANGAN MODUL PERPANGKATAN DAN BENTUK AKAR UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS - Kristiani Loi (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2022)
This research is motivated by the low ability of students to understand mathematical concepts, the lack of teaching materials that support the learning process and the teaching materials used are less attractive and difficult to reach. The research aims to produce a valid, practical, and effective power and root form module, as well as to improve students' mathematical concept understanding abilities. The research method uses research development (R&D) with a 4D model (Define, Design, Develop and Disseminate). The research instrument used a questionnaire and a test. Data analysis techniques are qualitative data analysis and quantitative data. Based on the results of the validity test, the percentage of material is 91.66%, the design is 85.5% and the language is 94% with very valid criteria. The results of the practicality test are based on the teacher's response, 90% of the criteria are very practical, the response of the limited trial is 80% of the practical criteria and the response of the field trial is 86.95%. The criteria are very practical. The results of the effectiveness test from the results of student learning tests for limited trials obtained an average of 74.80 criteria were quite effective and field trials 76.90 criteria were effective. The results of the N-gain analysis are the improvement of students' mathematical concept understanding abilities. For the limited trial 0.60 and the field test 0.58 with the medium category. Based on these results, it is said that the power and form module meets the valid, practical, and effective criteria and improves students' ability to understand mathematical concepts. The researcher suggests that this module can be used to improve the ability to understand mathematical concepts, especially in the matter of powers and roots.